Tool vibration due to high speed micro end milling parameters - Mohamed, Abd. Rahman; Atiqah, N.; Ali, Mohammad Yeakub; Chowdhury, M. S. H. (Trans Tech Publications Ltd., Switzerland, 2013)
This paper presents the effect of high speed micro end milling parameters on tool vibration during machining of poly(methyl methacrylate) (PMMA). The main focus is to achieve minimum tool vibration by controlling the cutting parameters; spindle speed, feed rate and depth of cut. An empirical model for tool vibration has been developed using Taguchi method. The orthogonal array, signal-to-noise ratio and analysis of variance revealed that high spindle speed is the most influential parameter to increase the level of tool vibration.